Designing outdoor environments for children landscaping schoolyards, gardens, and playgrounds - Tai, Lolly (McGraw-Hill, 2006)
This unique resource expertly details the design, installation, and maintenance of sustainable children's landscapes and play yards. Numerous case studies cover projects including storybook courtyards, music and barnyard gardens, nature trails, wildlife habitats, memorial, and edible gardens.